Periodicals & irregular serials - The Editors, - (Nordic Archaeological Abstracts - NAA, 1997)
Journals with papers abstracted in this number of NM are listed here. Addresses to the editor or publisher may be obtained by contacting the sub-editor or the members of the editorial board.